2014
DOI: 10.1152/ajplung.00154.2013
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β expression in the distal lung epithelium disrupts lung morphogenesis and epithelial cell differentiation in fetal mice

Abstract: Perinatal inflammation and the inflammatory cytokine IL-1 can modify lung morphogenesis. To examine the effects of antenatal expression of IL-1β in the distal airway epithelium on fetal lung morphogenesis, we studied lung development and surfactant expression in fetal mice expressing human IL-1β under the control of the surfactant protein (SP)-C promoter. IL-1β-expressing pups suffered respiratory failure and died shortly after birth. IL-1β caused fetal lung inflammation and enhanced the expression of keratino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 61 publications
2
27
2
Order By: Relevance
“…Although death in Cyp26b1 mutants was previously characterized as "respiratory distress" (Yashiro et al, 2004), RDS is characterized by decreased surfactant production from AT2 cells. In that regard, our work stands in contrast to other studies that have also identified similar defects in distal epithelial differentiation but found a decrease in surfactant production or proSP-C + AT2 cells (Compernolle et al, 2002;Hogmalm et al, 2014;Kersbergen et al, 2018;Rockich et al, 2013;Woik et al, 2014;Yang et al, 2002). Whereas the defects seen in these studies most likely arise from an inability of distal progenitor cells to first differentiate into AT2 cells, loss of Cyp26b1 appears to reduce the differentiation of distal progenitor into AT1.…”
Section: Discussioncontrasting
confidence: 99%
“…Although death in Cyp26b1 mutants was previously characterized as "respiratory distress" (Yashiro et al, 2004), RDS is characterized by decreased surfactant production from AT2 cells. In that regard, our work stands in contrast to other studies that have also identified similar defects in distal epithelial differentiation but found a decrease in surfactant production or proSP-C + AT2 cells (Compernolle et al, 2002;Hogmalm et al, 2014;Kersbergen et al, 2018;Rockich et al, 2013;Woik et al, 2014;Yang et al, 2002). Whereas the defects seen in these studies most likely arise from an inability of distal progenitor cells to first differentiate into AT2 cells, loss of Cyp26b1 appears to reduce the differentiation of distal progenitor into AT1.…”
Section: Discussioncontrasting
confidence: 99%
“…Given the known association of placental inflammation and FGR with decreased fetal lung development, we evaluated the influence of maternal HFD on fetal maturation (13,17). FGR is an independent risk factor for the development of chronic lung disease in the postnatal period (4,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The conditional expression of -1 causes severe pulmonary in lammation, alveolar hypoplasia, and progressive lung ibrosis, whereas the in vivo bloc age or depletion of -1 alleviates in lammation and ibrosis and ultimately prevents murine bronchopulmonary dysplasia [14,15]. Regarding the direct effects of -1 on the regulation of extracellular matrix (ECM) expression and composition, con licting data exist regarding the contributions of -1 to the development of myo ibroblasts, which are critical for alveolar formation [16][17][18].…”
mentioning
confidence: 99%